2014
DOI: 10.1016/j.jinorgbio.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Re(I) tricarbonyl complex of 1,10-phenanthroline-5,6-dione: DNA binding, cytotoxicity, anti-inflammatory and anti-coagulant effects towards platelet activating factor

Abstract: The complex fac-[Re(CO) 3 (phendione)Cl] (1) (where phendione=1,10-phenanthroline-5,6-dione) has been synthesized and fully characterized by UV-visible, FTIR, and NMR techniques.The DNA binding properties of 1 are investigated by UV-spectrophotometric (melting curves), covalent binding assay, CV (cyclic voltammetry), circular dichroism (CD) and viscosity measurements. Experimental data indicate that 1 fits into the major groove without disrupting the helical structure of the B-DNA in contrast to the free phend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(44 citation statements)
references
References 55 publications
0
38
0
1
Order By: Relevance
“…Kaplanis and coworkers [142] reported on a Re(I) derivative (Figure 8) of the general type fac -[Re(phendione)(CO) 3 Cl] ( Re-1 ) (where phendione = 1,10-phenanthroline-5,6-dione) that has been evaluated as inhibitor of PAF-induced aggregation of washed rabbit platelets (IC 50 = 0.86  μ M).…”
Section: Inorganic Metal-based Inhibitorsmentioning
confidence: 99%
“…Kaplanis and coworkers [142] reported on a Re(I) derivative (Figure 8) of the general type fac -[Re(phendione)(CO) 3 Cl] ( Re-1 ) (where phendione = 1,10-phenanthroline-5,6-dione) that has been evaluated as inhibitor of PAF-induced aggregation of washed rabbit platelets (IC 50 = 0.86  μ M).…”
Section: Inorganic Metal-based Inhibitorsmentioning
confidence: 99%
“…14). 51 Additionally, complex 41 and [Re(CO 5 )Cl] showed activity against PAF-basic metabolic enzyme activities in rabbit leukocyte homogenates. In cellular proliferation studies, the free ligand phendione was found to be highly cytotoxic towards a range of cancer cell lines, but this toxicity was markedly reduced upon complexation to Re( i ).…”
Section: Metal Complexes Of Anti-inflammatory Compoundsmentioning
confidence: 99%
“…It is hydrophobic and can behave as a π-acceptor chelator despite the poor σ-donor capability of the heteroaromatic nitrogen atoms [3]. Phen has further distinct chemical advantages, as its planarity allows phen complexes to intercalate with DNA and RNA via aromatic π-stacking [6]. In addition, the photochemical and photophysical properties of phen-based complexes has found application in catalysis, luminescent materials and bio-medical elds [7][8][9].…”
Section: Discussionmentioning
confidence: 99%